2023
DOI: 10.1057/s41599-023-01650-w
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality technology in enhancing learning retention and critical thinking according to STEAM program

Abstract: According to the science, technology, engineering, arts, and mathematics (STEAM) program, this experimental research aims to advocate e-content based on augmented reality (AR) technology to enhance retention learning (LR) and reinforce critical thinking in the intermediate stage in Ha’il, KSA. Then, we study the interaction between the technology of AR design (image/mark) and the mental capacity of learners (high/low) in developing critical thinking (CT) and practical skills, i.e., the interaction between AR (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
0
22
0
1
Order By: Relevance
“…Additionally, there are journals from the Q2 quartile, such as Computers in Human Behavior. Table 2 shows that the augmented reality topic is not only focused on specific science education but also related to the Journal of Human-Computer Studies (Heinrich et al, 2023), Journal PLOS ONE (Nakazawa et al, 2023), Journal Humanities and Social Sciences Communications (Alkhabra et al, 2023), the British Journal of Radiology (Lima et al, 2023), andJournal European Radiology (Farshad-Amacker et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, there are journals from the Q2 quartile, such as Computers in Human Behavior. Table 2 shows that the augmented reality topic is not only focused on specific science education but also related to the Journal of Human-Computer Studies (Heinrich et al, 2023), Journal PLOS ONE (Nakazawa et al, 2023), Journal Humanities and Social Sciences Communications (Alkhabra et al, 2023), the British Journal of Radiology (Lima et al, 2023), andJournal European Radiology (Farshad-Amacker et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Previous related works have adopted critical thinking as a critical factor under various STEAM courses (Alkhabra et al, 2023; Sha et al, 2021). For instance, Sha et al (2021) investigated the disparities in critical-thinking levels among college students with various levels of academic engagement in STEAM courses and revealed that the most critical thinking was displayed by students with a medium level of academic involvement.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For instance, Sha et al (2021) investigated the disparities in critical-thinking levels among college students with various levels of academic engagement in STEAM courses and revealed that the most critical thinking was displayed by students with a medium level of academic involvement. Alkhabra et al (2023) carried out an experimental study using augmented reality technology to improve eighth graders’ learning retention and critical thinking while gathering data on the learners’ mental capacity. They determined that the learners with high mental capacity exhibited better critical thinking than those with low mental capacity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Two types of modules have been developed in education: electronic and printed. The current information era helps us apply knowledge because it is built on digital technology (Alkhabra et al, 2023). One of the ways that teachers can try to face global challenges is by developing modules realized in digital form (emodules or electronic modules) (Nujuah & Winiarti, 2020).…”
Section: Introductionmentioning
confidence: 99%